2006
DOI: 10.1530/rep.1.01060
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on the association of idiopathic recurrent pregnancy loss with autoantibodies against β2-glycoprotein I and annexin V

Abstract: Whereas antiphospholipid antibodies (aPL) are associated with thrombotic events and recurrent spontaneous abortion (RSA), the contribution of anti-b2 glycoprotein 1 (b2GP1) and anti-annexin V antibodies as risk factors for RSA remain poorly understood. We investigated anti-b2-GPI and anti-annexin V IgM and IgG antibodies as potential risk factors for RSA in 200 women with more than three consecutive idiopathic RSA, and 200 age-matched, healthy, parous women. Pearson's chi squared test analysis showed that whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…In terms of the clinical importance of these antibodies, many authors suggest that a-A5 are an additional diagnostic marker in patients with different thrombotic conditions, reproductive problems and autoimmune diseases [2,9,15,19,28,31,32,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the clinical importance of these antibodies, many authors suggest that a-A5 are an additional diagnostic marker in patients with different thrombotic conditions, reproductive problems and autoimmune diseases [2,9,15,19,28,31,32,38].…”
Section: Discussionmentioning
confidence: 99%
“…The latter strongly correlated with the presence of recurrent miscarriages. In 2006, Zammiti et al [28] found that positive a-A5 and anti-b2GPI antibodies are independent risk factors for recurrent pregnancy loss.…”
Section: Significance Of Anti-annexin-a5mentioning
confidence: 99%
“…Nevertheless, serum levels of aβ2GP1 may be significantly elevated in aCL-negative patients with APS. A close correlation has been demonstrated between the presence of aβ2GPI-IgM and the occurrence of abortions during an early phase of pregnancy (17,18). Annexin V is one of the most significant placental anticoagulant proteins that can be detected in a reduced quantity from placentas of mothers with APS (15,16).…”
Section: Pregnancy Morbidity Amentioning
confidence: 95%
“…The risk of abortions during the late phase of pregnancy is particularly high in the presence of IgG isotype aANX antibodies (17,18). In addition, in the first trimester of pregnancy, aPLs may induce disorders of placentation and embryonal implantation by directly inhibiting hormone production and invasion of trophoblasts (15).…”
Section: Pregnancy Morbidity Amentioning
confidence: 99%
“…Moreover, it is suspected that anti-annexin V Ab may interfere with annexin V functions and exerts a detrimental role leading to thrombosis and/or vascular occlusion. 13 Nevertheless, there has been conflicting evidence regarding the correlation of Ab against annexin V with disease, with some studies indicating an association with clinical manifestations such as increased risk of pregnancy losses or thrombosis [14][15][16][17][18][19] whereas others have found this not to be the case. …”
mentioning
confidence: 99%